The Role of Law in Achieving Public Welfare - Ahmad Nizar Mohammad Syamwil; Reza Alfian Lubis (Program Pascasarjana UIN Sumatera Utara Medan, 2023)
The purpose of establishing a state is essentially to realize the welfare of the people. The government, as the state administrator, formulates this goal into responsive, aspirational, and progressive laws and regulations according to the needs of the community. To ensure that these laws are truly grounded, law enforcers, particularly judges as the spearhead of law enforcement, must not only focus on legal certainty (rechtsvaardigheit), but also prioritize the values of justice that live, grow, and develop within society. The role of law in realizing the welfare of the people must be reflected both in the substance of the law and the moral integrity of law enforcement officials, especially judges in adjudicating cases. Therefore, implementing the welfare of the people requires synergy between regulations that favor the public and law enforcement that is substantive, not merely procedural, justice. Justice directly experienced by the people is a primary indicator of achieving national prosperity.